Whispers on the color line : rumor and race in America - Fine, Gary Alan (University of California Press, 2001)
"Whispers on the Color Line focuses on a wide array of tales told in black and white communities across America. Topics run the gamut from alleged governmental conspiracies, possible food tampering, gang violence, and the sex lives of celebrities. Such beliefs travel by word of mouth, in print, and increasingly over the Internet. In many instances these rumors and legends reflect the tenaciousness of racial misunderstanding that continues to frustrate efforts to foster racial harmony, creating separate racialized pools of knowledge." "The authors have spent more than twenty years collecting and analyzing rumors and contemporary legends - from the ever-durable Kentucky Fried Rat cycle to persistent beliefs that athletic footwear manufacturers support white supremacist regimes. In this book, Fine and Turner explain how people find suspicious stories like these plausible. Telling them serves many purposes: to assuage anxieties, entertain friends, increase our sense of control - all without directly proclaiming our own attitudes. The authors consider how these tales reflect attitudes that blacks and whites have about each other and about the world they face. They brilliantly demonstrate how - by transforming unacceptable impulses into a narrative that is claimed to have actually happened - we are able to express the inexpressible."--Jacket